مكونات راس المال الفكري وتأثيرها في نجاح اعادة هندسة عمليات المنظمة : دراسة استطلاعية في الشركات العامة لانتاج الادوية و المستلزمات الطبية/نينوى - ميسون عبدالله احمد (PROSPECTIVE RESEARCHES, 2023)
The present study tackles each of the substances of intellectual capital and its influence on the success of re engineering business operations of the organization works within two frameworks; the first includes constituting an intellectual and field framework for determining the concept of intellectual capital and its contents, represented by human capital, structural capital, and customs capital, and their effect to the success of re engineering the operations of works. Generally, the research is an attempt to satisfy the following enquiries: 1. Do those who are in charge of the management of the organization have conception about the contents of intellectual capital? 2. Does the diagnosis of the contents of intellectual capital affect the success of the programs of re engineering in the surveyed organization? 3. Do the contents of intellectual capital affect the re engineering of the operations of the organization works? The research has come up with a group of conclusions in which the most important one is that the contents of intellectual capital in the surveyed organization can participate in implementing the operations of re engineering the operations of works. Depending on the conclusions which have been reached, a set of suitable suggestions have been put.